Calc-Alkaline Plutons in a Proto-Tethyan Intra-Oceanic Arc (Qilian Orogen, NW China): Implications for the Construction of Arc Crust. (29th December 2022) - Wang, Chao; Song, Shuguang; Zhao, Guochun; Allen, Mark B; Su, Li; Gao, Tianyu; Wen, Tao; Feng, Di
Abstract: Intra-oceanic arcs are one of the major building blocks of continents, and the rarely exposed calc-alkaline plutons in intra-oceanic arcs are a critical component of arc crust. These calc-alkaline plutons provide juvenile crustal materials to the continental crust, and thus their petrogenesis has important implications for the formation and evolution of continental crust. Here, we present the results of an integrated study, involving field investigation, petrology, geochronology and geochemistry, on calc-alkaline intermediate–felsic plutons and their mafic magmatic enclaves (MMEs) within a Proto-Tethyan intra-oceanic arc in the Lajishan terrane of the Qilian Orogen, northern Tibetan Plateau. These calc-alkaline intermediate–felsic plutons range from gabbroic diorites, through diorites, to granodiorites. In situ zircon U–Pb dating demonstrates that these plutons were emplaced in the Early Paleozoic (474–460 Ma), slightly older than previously identified 460–440 Ma intra-oceanic arc volcanics (boninites, ankaramites, high-Mg basaltic andesites, high-Al andesites, sanukites) in the Lajishan terrane. The geochemistry of these plutons indicates that they were differentiation products of subduction-metasomatized arc mantle-derived melts, and isotope modeling constrains that their mantle source was metasomatized by less than 10% addition of slab-derived fluids/melts. Their parental melts experienced polybaric medium- to high-pressure fractional crystallization to generate the compositional variation of these plutons. There are two types of MMEs according to their different geochemistry (high- and low-MgO MMEs) and both of them are early crystallized melts derived from the heterogeneous subduction-metasomatized arc mantle wedge, captured by evolving magmas. Alkaline high-MgO MMEs represent near-primitive alkaline melts derived from melting of pyroxenite with phlogopite-enriched veins in the heterogeneous arc mantle wedge, while low-MgO MMEs stand for relatively evolved calc-alkaline melts formed during differentiation of the melts parental to their host. The upper crustal construction of this Proto-Tethyan intra-oceanic arc was achieved through earlier emplacement of 474–460 Ma calc-alkaline plutons followed by slightly later eruption of arc volcanics at 460–440 Ma above these plutons. As approximated by the composition of these calc-alkaline plutons and arc volcanics, the upper crustal composition of this Proto-Tethyan intra-oceanic arc is still juvenile and primitive. This juvenile intra-oceanic crust was accreted to continental blocks through arc–continent collision at 440–420 Ma, in response to closure of the Proto-Tethys Ocean. The accreted intra-oceanic crust represents addition of juvenile crustal materials to existing continents and has remained primitive and intact, which could be balanced by other more evolved crustal components to form a mature bulk continental crust.